Improvement in gravel-mulched land soil nutrient and bacterial community diversity with Lonicera japonica - Wang, Xing; Ma, Bin; Liu, Hua; Bao, Yangmei; Li, Ming; McLaughlin, Neil B.; Guo, Lanping (Frontiers in Microbiology, 2023)
Gravel-mulched land in China suffers from poor natural resources and fragile ecological environment, posing a challenge to effective restoration of ecological function. Lonicera japonica, a traditional Chinese herb used for treating human diseases, is a highly adaptable and resilient plant species, can effectively improve the soil properties, and may have important implications for the ecology and economy of gravel-mulched land. A study was conducted in a gravel-mulched field to measure the impact of planting the L. japonica (including control (CK), 1-year, 2-year, and 4-year cultivation of plants) on (i) dynamic changes in soil nutrient and enzyme activity properties, and (ii) soil rhizosphere microbial community structure characteristics. We found that the concentration of soil organic carbon, available nitrogen, available phosphorus and available potassium in L. japonica soil after cultivation for 1-4 years increased by 11%-409%. The urease, phosphatase and catalase activities were increased by 11%-560%, with the highest nutrient concentration and enzyme activity in 4-year plants. The pH value gradually decreased after cultivation. The improved soil environments increased soil bacterial community diversity. Planting L. japonica significantly increased the bacterial ACE, Chao1 index, Simpson index, and Shannon-Wiener index. The Firmicutes, Proteobacteria and Bacteroidetes were observed in dominant phyla. The relative abundance of eight genera, including Streptococcus, Veillonella and Rothia, was significantly reduced by more than 1%.Taken together, these soil indicators suggest that planting L. japonica in the short term would be a cost-effective strategy to combat soil degradation in a gravel-mulched ecosystem.